Preparation and Characterization Evaluation The Zno Nanoparticles on Lymphocyte Vitality: Persiapan dan Evaluasi Karakterisasi Nanopartikel Zno pada Vitalitas Limfosit - Lateff, Nedhal Ibrahim; Al-Obaidi, Fiham Jassim; Hameed, Ashwaq Talib; Saleh, Eman Naji (Indonesian Journal on Health Science and Medicine, 2024)
The oxidase-positive, motile, Gram-negative bacteria Plesiomonas shigelloides is found all across the natural world. Additionally, it is a major pathogen that mostly causes disorders of the intestines in humans. Most of these illnesses are characterised by diarrhoea, which may be watery, invasive, or chronic in nature. There have been reports of intestinal illnesses caused by Plesiomonas that were spread by food and water. There are a number of extraintestinal diseases caused by P. shigelloides, the most prevalent of which are sepsis and meningitis, both of which are associated with significant fatality rates. Phylogenetically closely related to other Enterobacteriaceae species, P. shigelloides differs biochemically from them. A single biovar, with over a hundred serovars documented. Some have proposed P. shigelloides as a "natural" vaccination against shigellosis since it is thermo-, alkali-, acido-, and halotolerant. There are some intestinal media that are known to limit the development of Plesiomonas, and in the lab, it looks barely there on the surface of many agar plates. The antibiotic sensitivity patterns of Plesiomonas are somewhat peculiar, and the amount of the inoculum determines how susceptible the bacteria are to certain drugs. One distinguishing feature of high bacterial densities in the presence of certain β-lactam antibiotics is the development of significant cell filamentation Highlights: Pathogen: Causes diarrheal diseases, sepsis, and meningitis in humans. Characteristics: Gram-negative, motile, tolerates heat, alkali, acid, and salt. Antibiotics: Susceptibility varies; β-lactams cause cell filamentation in high densities. Keywords: Plesiomonas shigelloides, bacteria, diarrhea